2017
DOI: 10.1038/srep45834
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of axial macrosegregation of primary phases induced by a static magnetic field during directional solidification

Abstract: Understanding the macrosegregation formed by applying magnetic fields is of high commercial importance. This work investigates how static magnetic fields control the solute and primary phase distributions in four directionally solidified alloys (i.e., Al-Cu, Al-Si, Al-Ni and Zn-Cu alloys). Experimental results demonstrate that significant axial macrosegregation of the solute and primary phases (i.e., Al2Cu, Si, Al3Ni and Zn5Cu phases) occurs at the initial solidification stage of the samples. This finding is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The appropriate magnitude of TEMC results in a stability in the liquid-solid interface 27 . However, the strong TEMC could modify the liquid-solid interface shape and the dendrite morphology, or induce the macrosegregation 22 24 , 45 , 46 . The two effects compete.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate magnitude of TEMC results in a stability in the liquid-solid interface 27 . However, the strong TEMC could modify the liquid-solid interface shape and the dendrite morphology, or induce the macrosegregation 22 24 , 45 , 46 . The two effects compete.…”
Section: Discussionmentioning
confidence: 99%
“…These currents interact with an externally applied magnetic field, generating a thermoelectric Lorentz force (TEF) that drives flow through a phenomenon known as thermoelectric magnetohydrodynamics (TEMHD). The TEMHD effect, also known as thermoelectric magnetic convection (TEMC), has been shown to introduce many changes to the microstructure, including macrosegregation [5][6][7] that leads to a tilted interface, 8 the formation of solute pockets, 6,9 banded structures, 10 modification to the primary arm spacing, 11 and the formation of stray grains in single-crystal castings. 12 Most of the cited studies were carried out on alloys where the solute density was higher than in the bulk liquid, hence solute plumes do not spring from the interface; however, similar changes are also observed in systems where the solute is the lighter element.…”
Section: Introductionmentioning
confidence: 99%
“… 13 modeled the mechanism of magnetic field induced macrosegregation and dendritic refinement that demonstrated that static magnetic fields lead to a large scale flow circulation in the liquid phase. Experimental results have shown that the application of a static magnetic field during directional solidification could induce the formation of thermoelectric magnetic convection (TEMC) 14 17 . The initial driver for TEMC is indentified as Lorentz force in the liquid phase caused by the interaction of thermoelectric current and the magnetic field 18 .…”
Section: Introductionmentioning
confidence: 99%